2004
DOI: 10.1002/star.200300238
|View full text |Cite
|
Sign up to set email alerts
|

Acylation of Starch with Vinyl Acetate in Water

Abstract: Acetylation of different types of starch with vinyl acetate in water in the presence of a base is described. Maximum degree of substitution under these conditions is 1.1. Vinyl esters of higher homologous acids (vinyl laurate) react very slowly giving very low degrees of substitution after long reaction times. The reaction mixture is biphasic, because vinyl esters are not miscible with water. Formation of two layers reduces loss of acylating agent due to reaction with water – which is a major problem encounter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 5 publications
1
24
0
Order By: Relevance
“…It has been reported that polysaccharides such as starch, cyclodextrins, or cellulose can be successfully esterified in homogeneous or heterogeneous conditions by reaction with vinyl esters 23–28. More recently, we showed that lignocellulosic materials such as wood can be easily esterified in mild conditions by this method 29–31.…”
Section: Introductionmentioning
confidence: 89%
“…It has been reported that polysaccharides such as starch, cyclodextrins, or cellulose can be successfully esterified in homogeneous or heterogeneous conditions by reaction with vinyl esters 23–28. More recently, we showed that lignocellulosic materials such as wood can be easily esterified in mild conditions by this method 29–31.…”
Section: Introductionmentioning
confidence: 89%
“…The starch peaks (d 3-5.5 ppm) are broad and overlapping [10]. This feature hampers the DS determination by NMR, and therefore a peracetylation procedure to substitute all of the remaining OH groups with acetate groups was applied [8,10,11]. The 1 H-NMR spectrum of a typical peracetylated starch laurate is shown in Fig.…”
Section: H-and 13 C-nmr Analysesmentioning
confidence: 99%
“…Recently Mormann et al [8] explored the possibility of using vinyl esters and particularly vinyl acetate as reagents for the preparation of starch esters. Their re-search focused on the synthesis of starch acetates and only two examples of a reaction with a higher fatty acid vinyl ester were reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, the degree of substitution (DS) is still low and the catalyst is expensive too. Very recently, two reports appeared in the literatures that use a base catalyzing acetylation of starch [13] and sucrose [14] with vinyl acetate in water. Because vinyl acetate is not sensible and miscible with water, the reaction mixture forms two layers reducing loss of acylating agent due to reaction with water, which is a major problem encountered for acetylation with acetic anhydride.…”
Section: Introductionmentioning
confidence: 99%